1979
DOI: 10.1111/j.1365-2672.1979.tb02586.x
|View full text |Cite
|
Sign up to set email alerts
|

The Anti‐Endotoxin Activity of Taurolin in Experimental Animals

Abstract: Taurolin, a broad spectrum bactericidal agent, protected experimental animals from the lethal effects of Escherichia coli and Bacteroides fragilis endotoxin. Taurolin also prevented the pyrexic response of rabbits to TAB vaccine. Results suggest that Taurolin exerts its antiendotoxic effect by direct reaction with the endotoxin molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 2 publications
1
9
0
1
Order By: Relevance
“…Therefore, we conclude that intraperitoneal application of a single dose of taurolidine is inappropriate for bacterial kill ing. Taurolidine is known to inactivate endo toxins in vitro [22] as well as in vivo [30] which is corroborated by the results of our study. The endotoxin concentrations in the abdominal cavity and in plasma in the taurolidine-treated group were significantly lower than those in the saline group in the first 6 h.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, we conclude that intraperitoneal application of a single dose of taurolidine is inappropriate for bacterial kill ing. Taurolidine is known to inactivate endo toxins in vitro [22] as well as in vivo [30] which is corroborated by the results of our study. The endotoxin concentrations in the abdominal cavity and in plasma in the taurolidine-treated group were significantly lower than those in the saline group in the first 6 h.…”
Section: Discussionsupporting
confidence: 82%
“…Similar to CHX, taurolidine generally did not show any bacterial resistance due to this relatively unspecific pathway [34,35]. Since it is used in abdominal surgery and on mucous membranes, it can be suggested that it can be irrigated on mucosal tissues without damage to soft tissues or bone.…”
Section: Introductionmentioning
confidence: 99%
“…CLS is a mixture of taurolidine -an antimicrobial substance -, citric acid and citrate for anticoagulation. Taurolidine is a unique nontoxic substance with antimicrobial [2], antimycotic [3], antiadherent [4] and antiendotoxic [5] properties. It is effective against multiresistant bacteria [6] and also inhibits staphylococcus coagulase [7], a clotting activator not inhibited by heparin, hirudin or antithrombin.…”
Section: Methodsmentioning
confidence: 99%